A review on phonological awareness and visual-spatial ability among children with dyslexia - Chong, Agnes Shu Sze; Normah Che Din,; Norhayati Ibrahim,; Mahadir Ahmad,; Rogayah Abdul Razak,; Pheh, Kai Shuen (Penerbit Universiti Kebangsaan Malaysia, 2018)
This review aims to present an overview of current research findings on the possible relationship between phonological awareness and visual-spatial skills among individuals with dyslexia. Narrative review of the relevant articles were obtained through computerized searches of databases such as PubMed, PubMed Central (PMC) and Google Scholar which included articles from SAGE, Taylor & Francis and Massachusetts Institute of Technology (MIT) Press from the year 2000 to 2014. The key words were explored, both exclusively and in combination with each other, so as to provide a better understanding of the relationship between them among individuals with dyslexia. Although it is evident that there is a phonological deficit in individuals with dyslexia, however, it is inconclusive with regards to the visual-spatial deficit and strength. There is a consensus on the nature of phonological awareness skill deficits but not on the visual spatial abilities in dyslexia. In fact, the relationship between phonological awareness and visual spatial abilities in dyslexia is dependent on the area of visual ability measured.